Analysis of Liquidity Ratios and Profitability Ratios as a Measure of Financial Performance of PT. OMI - Tiana, Rizka Nurul; Jefri, Riny (Jurnal Ekonomi Lembaga Layanan Pendidikan Tinggi Wilayah I, 2025)
This purpose of this study how to the financial capacity of the company PT. OMI use financial ratio tools, namely liquidity ratios, effectively, which has been established since 2020. The method use is descriptive quantitative, with the type of data being secondary data in the form of PT. OMI’s financial statements from 2022-2024. The results of the liquidity ratios by the Current Ratio shows a liquid with an average of 1,25 (times) above the industry standard ratio of 1 (times). Quick Ratio with an average og 0,93 (times) below the industry standard ratio of 1,5 (times). PT. OMI is unable to settle its debts using current assets while reducing inventory. Therefore, PT. OMI can only meet its debts by relying on total current assets. Analysis of profitability ratios shows poor performance as the average NPM is -10,4%, ROA is -5,4%, and ROE is -23%. Indicates that the results of these three profitability ratios are not good, as they are significantly below the industry standard. This implies that PT. OMI lacks the ability to acquire and manage capital to generate profit. This ratio measurement tool is very effective in assessing PT. OMI’s current financial performance and serves as a basis for management evaluation.